Authorship: From credit to accountability. Reflections from the Editors´ Network - Alfonso, Fernando; Zelveian, Parounak; Monsuez, Jean-Jacques; Aschermann, Michael; Boehm, Michael; Hernandez, Alfonso Buendia; Wang, Tzung-Dau; Cohen, Ariel; Izetbegovic, Sebija; Doubell, Anton; et al. (SA Heart Journal, 2019)
The Editors´ Network of the European Society of Cardiology (ESC) provides a dynamic forum for editorial discussions and endorses the recommendations of the International Committee of Medical Journal Editors (ICMJE) to improve the scientific quality of biomedical journals. Authorship confers credit and important academic rewards. Recently, however, the ICMJE emphasised that authorship also requires responsibility and accountability. These issues are now covered by the new (fourth) criterion for authorship. Authors should agree to be accountable and ensure that questions regarding the accuracy and integrity of the entire work will be appropriately addressed. This review discusses the implications of this paradigm shift on authorship requirements with the aim of increasing awareness on good scientific and editorial practices.